A Study on ESG Evaluation Indicators Through Chemical Accident Data Analysis and Double Materiality Assessment - Yoon, Cheolhee; Kwak, Hyunjun; Jung, Seungho (Processes, 2025)
This study focuses on identifying key factors that companies should prioritize to prevent chemical accidents from an ESG (Environmental, Social, and Governance) perspective. ESG provides insight into corporate sustainability by comprehensively considering both external impacts and internal risks. To achieve this, this study applied a scoring approach based on double materiality, assessing both internal and external impacts. The assessment process involved data collection, categorization of accident causes, score calculation, and prioritization of safety management items. Data from chemical accident statistics revealed that mechanical integrity, human factors, and preventive maintenance were the primary causes across all three countries. Internal impacts were evaluated by accident severity and frequency, while external impacts considered casualties and management priorities. Internal impact results showed mechanical integrity as critical in the U.S., preventive maintenance in the U.K., and human factors in Republic of Korea. For external impacts, human factors were most critical in Republic of Korea. To prioritize safety management elements for chemical accident prevention from an ESG perspective, this study categorized them into three tiers. Tier 1 represents the most critical elements requiring urgent attention, while Tier 3 includes the least critical elements. This tier classification is intended not as an absolute ranking but as a general reference for identifying overall trends in safety management priorities. Tier 1 included the U.K.’s preventive maintenance and human factors across all countries, with Republic of Korea’s human factors being the most vulnerable. Tier 2 revealed operating procedures and human factors as critical, with U.S. emergency preparedness and U.K. design highlighted. Tier 3, with impact scores below 1, was safest. These findings effectively identified safety management priorities to enhance accident prevention.
Keywords: Chemical accident; Chemical safety; Critical elements; Double materiality; Environmental, social, and governance; Materiality assessment; Mechanical integrity; Occupational health and safety; Republic of Korea; Safety management; chemical safety; double materiality; ESG; Materiality assessment; occupational health and safety